Evaluasi Penggunaan E-Learning Universitas Universal Mobile Dengan Metode Goal Directed Design - Kusuma, Candra; Charless (Journal of Digital Ecosystem for Natural Sustainability, 2022)
Universitas Universal currently has an official website-based E-Learning application that can be accessed by user account via mobile devices and desktops. However, after being given several questionnaires to the respondents, there were several shortcomings that needed to be corrected in the mobile version of the E-Learning application. The purpose of this study was to evaluate the level of usability and effectiveness of the interface design on the mobile version of Universitas Universal E-Learning. The method used is the Goal Directed Design method. This research was also conducted using the System Usability Scale (SUS) calculation technique to measure the usability level. The result of this research is the user interface design which is made based on the stages in the Goal Directed Design method, namely research, modelling, requirements, framework and refinement. The conclusion of this research is that there is an increase in the level of usability in the new user interface design from an average score of 78 to 85 and the criteria for acceptable are acceptable in the acceptability ranges, found in Grade B, and the criteria for excellent in adjective ratings were previously only acceptable on acceptability ranges, found in Grade C, and good criteria on adjective ratings.